PENGARUH ANTARA LAMA MENDERITA DIABETES MELITUS TIPE II DENGAN TERJADINYA VERTIGO PERIFER - PURWATININGSIH, RATNA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Type II diabetes mellitus (DM II) cause microangiopathy and makroangiopati, one of which may cause damage to the vestibular organ in the inner ear. The vestibular disorders can cause vertigo complaints. Several studies have shown that long type II ≥D M5 years predisposes microangiopathic complications in patients with diabetes mellitus type II. This study aims to determine whether the duration of type II DM ≥ 5 years have a greater risk for peripheral vertigo occur than the duration of DM <5 years. This study used a case-control study design with retrieval of medical records. The subjects were patients with a diagnosis of peripheral vertigo, with control patients with DM II routine control in clinic and inpatient hospital DR.Sardjito, which are grouped into two groups consisting of 33 subjects with a diagnosis of peripheral vertigo and 33 subjects without complaints of vertigo. Subjects consisted of 45 women and 21 men, with a mean age of 55 ± 9.6 years. In bivariate analysis, obtained age, history of hypertension, diabetes mellitus type II long time increases the risk of peripheral vertigo and statistically significant. In multivariate analysis, the variables age is an independent risk factor for the occurrence of peripheral vertigo (OR = 3.456; 95% CI 1.096 to 10.89, while the duration of type II diabetes mellitus and a history of hypertension is not an independent risk factor and not statistically significant Duration of DM ≥ 5 years have a tendency to occur peripheral vertigo compared with the duration of DM <5 years.